THE INTERACTION PATTERNS OF ALLAH PROTECTION TOWARDS MANKIND FROM SYAITAN’S INTERFERENCE - Safa'at Ariful Hudha (Jurnal Ilmiah Pesantren, 2019)
The aim of writing this paper is to reveal the patterns of Allah protection towards mankind from the syaitan’s interference and his viciousness through interaction of the relationship between Allah and human. The nature of Allah that consist of tauhid rububiyah, mulkiyah and tauhid uluhiyah are the basis of attachment relationship between Khaliq and makhluq, both of them are interacting one another. Those three natures of Allah are contained in QS. An-Naas, the 114thsurah in the Holy Qur’an. As a makhluq, Human who were being created by the Khaliq were highly recommended to seek refuge only unto Him, The Protector and The Sovereign Lord of mankind, and the only one God who has to worship, ask for his protection from the viciousness of syaitan khannas, which was whispering into the chest and invisible by the man.